A validation study of the Malay version of the job stress level inventory - Rasudin, Nur Syahmina; Shohaimi, Shamarina; Hassan, Siti Aishah; Zainuddin, Huda (Redfame Publishing, 2016)
Job stress has been identified as one of the most widespread problems for many years. Hence, a validated and reliable instrument is very important for measuring the level of job stress among employees. About 210 secondary school teachers from 30 schools in Kota Bharu district participated in this study. The sample size was divided half into Exploratory factor analysis (EFA) and Confirmatory Factor Analysis (CFA). The instrument was answered by respondents by self-administered. Data was analyzed for EFA, CFA, internal consistency and convergent validity using STATA software version 14. The EFA resulted in reduction of items from 20 to 18, which comprised of 2 factors. Meanwhile, the CFA results exhibited that the data fitted the model very well with Chi square/df (1.488), CFI (0.944) and TLI (0.934) and RMSEA (0.069). The two factors of Job Stress Level Inventory were renamed as Job Performance and Intention to Withdraw. Overall JSLI produced very good internal consistency with Cronbach’s alpha value of 0.93. The Average Variance Extracted (AVE) value of JSLI is 0.51 indicate that the convergent validity is met. Two factors produced by EFA consist of 17 items were named as Behavioural Symptom and Motivational Symptom that measuring the job stress level of employee. Job Stress Level Inventory was concluded to be a reliable and validated instrument in measuring the level of job stress among school teachers and also can be used to assess the job stress level of employee from other fields of work.